2020
DOI: 10.3390/nu12030656
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Serum Zinc Levels on Abdominal Fat Mass in Hemodialysis Patients

Abstract: Background: Zinc deficiency is highly prevalent and is caused by inadequate dietary intake, malabsorption and removal by treatment in hemodialysis patients. This study investigated the relationship between serum zinc levels and nutritional status in hemodialysis patients. Methods: A cross-sectional study examining 87 hemodialysis patients was performed. The serum concentrations of zinc were studied to evaluate their association with nutritional status, which was assessed by measuring abdominal muscle and fat a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Linearity of the calibration curve above 0.999 was obtained for both trace metals in the range from 1 to 250µg/L. The accuracy of the method used, expressed as recovery and determined by analysis of standard reference material (Seronorm TM Trace Elements Serum L-2), was from 95.2 to 103.3% for 65 Cu and from 96.2 to 102.7% for 66 Zn. Serum zinc concentration below 60 µg/dL was defined as zinc deficient (50).…”
Section: Serum Zinc and Copper Determinationmentioning
confidence: 83%
See 1 more Smart Citation
“…Linearity of the calibration curve above 0.999 was obtained for both trace metals in the range from 1 to 250µg/L. The accuracy of the method used, expressed as recovery and determined by analysis of standard reference material (Seronorm TM Trace Elements Serum L-2), was from 95.2 to 103.3% for 65 Cu and from 96.2 to 102.7% for 66 Zn. Serum zinc concentration below 60 µg/dL was defined as zinc deficient (50).…”
Section: Serum Zinc and Copper Determinationmentioning
confidence: 83%
“…Some authors declare that it is not clear yet whether low serum/plasma zinc levels in CKD patients represent genuine deficiency or its low levels are due to redistribution in different biological compartments ( 65 ). Recently, serum zinc levels were found to positively correlate with the nutritional status assessed by measuring abdominal fat area using computed tomography in patients with advanced CKD undergoing hemodialysis ( 66 ). In our study, no statistically significant correlations were determined between the serum zinc level concentration and anthropometric measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigated serum zinc levels and the nutritional status in maintenance HD patients. Serum zinc levels were found to positively correlate with the nutritional status in HD patients, which was assessed by measuring abdominal fat areas using computed tomography [ 15 ]. Furthermore, a previous meta-analysis revealed that zinc supplementation improved the nutritional status of maintenance HD patients [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study on maintenance HD patients recommended a lower serum zinc range (≤78.3 µg/dL) because of the potential for copper deficiency [ 14 ]. Previous studies suggested that a relationship exists between serum zinc levels and the nutritional status [ 15 , 16 ]; however, limited information is currently available on this relationship in HD patients. Furthermore, although serum zinc levels may affect the outcomes of CVD and mortality, their relationship with clinical outcomes remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Beddhu et al [ 47 ] have attempted to answer this question using 24-h urinary creatinine excretion as a marker for muscle mass in conjunction with BMI and proposed that muscle mass might be more important in this survival advantage than fat mass. Besides, Caetano et al [ 48 ] have demonstrated that fat mass might be more important than muscle mass in predicting 1-year mortality with bioimpedance analysis.…”
Section: Zinc and Nutrition In Ckdmentioning
confidence: 99%